The identification of hydrographical watershed headwaters - methods and applications - Meléndez de la Cruz, Juan Felipe (2019)
Watersheds are large natural units where the hydrological cycle takes shape in the continents, with water being the central element. Normally, these units are delimited qualitatively considering a continuous dividing line that roughly joins the points of the high parts of positive geoforms such as mountains or hills. Taking into account the natural criterion of drainage, the watershed is structured by a network of streams or channels and in turn can be classified or sorted. The aforementioned drainage network is subdivided into sub-basins, one or two of these can give rise to the main current that is normally a river and in turn determine the head of the basin. The classification of drainage basins is one of the methods known universally to delimit units and subunits and that must be taken into account to solve the problems of delimitation of headwaters of watersheds in our country. Currently, in our country there is a need to identify technical criteria to identify headwaters of watersheds. This work seeks to contribute to the referred technical requirement from the academic point of view.